(x+y)^2-(3x-2y)^2计算
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 11:41:53
(x+y)^2-(3x-2y)^2计算(x+y)^2-(3x-2y)^2计算(x+y)^2-(3x-2y)^2计算(x+y)^2-(3x-2y)^2=x²+2xy+y²-(9x
(x+y)^2-(3x-2y)^2计算
(x+y)^2-(3x-2y)^2计算
(x+y)^2-(3x-2y)^2计算
(x+y)^2-(3x-2y)^2
=x²+2xy+y²-(9x²-12xy+4y²)
=x²+2xy+y²-9x²+12xy-4y²
=-8x²+14xy-3y²
-8x^2-3y^2+14x*y
计算:(x+3y)(2x-y)
计算:(2x-3y)(x+y)
计算:(-x-2y) * (3x-y)
计算:(x+y)-3(x-2y).
计算(x-y)^2×(x-y)^3×(y-x)×(y-x)^2
计算2/3x-2/x+y(x+y/3x-x-y)/x-y/x
(x-2y)(x+y)+(x+y)计算
计算(x+y)(x+y)^2(-x-y)^3
3x(x-y)+2y(x-y) 计算
计算:(x-y)^2-(x+y)(x-y)
计算:x+2y/x-y+2x/y-x-3y/x-y
(x+y)^2-(3x-2y)^2计算
计算x^2y^-3(x^-1y)^3
因式分解(-x-2y)(3x-y)计算
计算:(x-3y)(x+2y)
计算:y×(y/x)^3÷[-(x^2)/y]^-2
计算:y(x-y)^2+(y-x)^3=?
-2x(3x-7y)+(x-y)(x^2+xy+y^2) 计算